Resolution of the type material of the Asian elephant, Elephas maximus Linnaeus, 1758 (Proboscidea, Elephantidae). (4th November 2013) - Cappellini, Enrico; Gentry, Anthea; Palkopoulou, Eleftheria; Ishida, Yasuko; Cram, David; Roos, Anna‐Marie; Watson, Mick; Johansson, Ulf S.; Fernholm, Bo; Agnelli, Paolo; Barbagli, Fausto; Littlewood, D. Tim J.; et al.
<x xml:space="preserve">Abstract</x> The understanding of Earth's biodiversity depends critically on the accurate identification and nomenclature of species. Many species were described centuries ago, and in a surprising number of cases their nomenclature or type material remain unclear or inconsistent. A prime example is provided by Elephas maximus, one of the most iconic and well‐known mammalian species, described and named by Linnaeus (1758) and today designating the Asian elephant. We used morphological, ancient DNA (aDNA), and high‐throughput ancient proteomic analyses to demonstrate that a widely discussed syntype specimen of E. maximus, a complete foetus preserved in ethanol, is actually an African elephant, genus Loxodonta. We further discovered that an additional E. maximus syntype, mentioned in a description by John Ray (1693) cited by Linnaeus, has been preserved as an almost complete skeleton at the Natural History Museum of the University of Florence. Having confirmed its identity as an Asian elephant through both morphological and ancient DNA analyses, we designate this specimen as the lectotype of E. maximus. The mass spectrometry proteomics data have been deposited in the ProteomeXchange Consortium with the data set identifier PXD000423. © 2013 The Linnean Society of London